PERBEDAAN KADAR TRIGLISERIDA DARAH PADA PEROKOK DAN NON-PEROKOK MAHASISWA FAKULTAS TEKNIK UISU: DIFFERENCES IN BLOOD TRIGLYCERIDE LEVELS IN SMOKERS AND NON-SMOKERS OF ENGINEERING FACULTY UISU - Handayani, Maya Putri; Aktalina, Lucia; Oktaria, Selly; Lubis, Ichwan Alamsyah (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2026)
Tobacco smoking is one of the largest public health burdens in the world. Cigarettes contain various toxic chemicals, including tar, carbon monoxide (CO), and nicotine, which are the main components with detrimental effects on health. Nicotine increases the secretion of catecholamines, which trigger lipolysis or the breakdown of fat in the body. This process lowers the levels of HDL which are beneficial for the body, while increasing triglycerides, bad cholesterol such as LDL, VLDL, and total cholesterol. This study aims to determine the differences in blood triglyceride levels between smoking and non-smoking students at the Faculty of Engineering, UISU. This study used an analytical survey method with a cross-sectional design. Sampling used a purposive sampling technique with a total of 47 people. The results of this study data were conducted through univariate and bivariate tests with an independent sample t test. The results of the univariate test included 35 smoker respondents and 12 non-smokers. The average triglyceride results of smoker respondents were 176.14 (± 29.76) and non-smokers 146.17 (± 20.36). The results of the bivariate test on the difference in blood triglyceride levels between smokers and non-smokers found a p-value of 0.002. There was a significant difference between blood triglyceride levels in smokers and non-smokers in students at the Faculty of Engineering, UISU. AbstrakMerokok tembakau merupakan salah satu beban kesehatan masyarakat terbesar di dunia. Rokok mengandung berbagai bahan kimia beracun, termasuk tar, karbon monoksida (CO), dan nikotin, yang merupakan komponen utama dengan efek merugikan pada kesehatan. Nikotin meningkatkan sekresi katekolamin, yang memicu lipolisis atau pemecahan lemak dalam tubuh. Proses ini menurunkan kadar HDL yang bermanfaat bagi tubuh, sekaligus meningkatkan trigliserida, kolesterol jahat seperti LDL, VLDL, serta kolesterol total. Penelitian ini bertujuan untuk mengetahui perbedaan kadar trigliserida darah antara mahasiswa perokok dan non- perokok di Fakultas Teknik UISU. Penelitian ini menggunakan Metode survey analitik dengan rancangan cross-sectional. Pengambilan sampel menggunakan teknik Purposive Sampling dengan jumlah 47 orang. Hasil data penelitian ini dilakukan melalui uji univariat dan bivariat dengan uji independent sample t test. Hasil uji univariat terdapat responden perokok 35 orang dan non perokok 12 orang. Hasil rata-rata trigliserida responden perokok 176,14 (± 29.76) dan non perokok 146,17 (± 20.36). Hasil uji bivariat tentang perbedaan kadar trigliserida darah pada perokok dan non perokok didapati nilai p=0,002. Terdapat perbedaan signifikan antara kadar trigliserida darah pada perokok dan non perokok pada mahasiswa di Fakultas Teknik UISU.